Mapping QTLs for reaction to powdered mildew and to angular leaf spot in common beans under different environments - Melo, Leonardo Cunha; dos Santos, João Bosco; Ferreira, Daniel Furtado (Pesquisa Agropecuaria Brasileira, 2002)
The objectives of this work were to identify, under different environments, RAPD markers linked to QTLs (Quantitative Trait Loci) that control the reaction to powdered mildew and to angular leaf spot a segregating population of common beans, to evaluate the existence of interactions involving QTLs with planting dates and to compare detection procedure of markers linked to QTLs utilizing the methods of mapping and multiple regression. One hundred and ninety-six recombinant inbred lines derived from the cross of cultivars Carioca x Flor de Mayo under two traditional sowing dates were evaluated for common beans (drought for evaluating the angular leaf spot, and winter for evaluating the powdered mildew) in 1996, 1997 and 1998, in two localities of Minas Gerais State, Brazil. For the phenotypic evaluation of the families, seven field experiments were conducted. The experimental design used was a 14x14 partially balanced square simple lattice. Results indicated that interaction of QTLs by local were significant, and some QTLs with stability were identified. Multiple regression analysis identified a greater number of QTLs-linked markers than the process of composite interval mapping. There was no coincidence between results obtained with the two methods for the majority of the traits studied. Molecular markers which were considered of greater potential use on marker-assisted selection were OPR02-832, OPD08-759 and OPN10-851 for reaction to powdery mildew and OPN02-436, and OPN07-1072 for reaction to leaf blight.